Spatio-temporal evolution of water engineering facilities and social influences on the Grand Canal during the Ming and Qing dynasties - Wang Cheng; Tan Lifeng; Wang Guanhua; Li Liang; Qiu Xin; Zhang Yiwen (Heritage Science, 2024)
Abstract This research explores the spatial distribution patterns of water engineering facilities along the Grand Canal during the Ming and Qing dynasties. It employs the entropy method to assess the social development status of prefectures during these periods and uses the Tobit model to examine the primary indicators influencing the distribution of water engineering facilities. The results show that the spatial distribution pattern of water engineering facilities was characterized by aggregation during the Ming and Qing dynasties. In contrast, the Qing dynasty’s distribution was more dispersed, with a shift in the construction focus of water engineering facilities towards the south. The spatial distribution pattern of water engineering facilities in the Ming Dynasty centered around the hotspot areas of Shuntian Prefecture, Yanzhou Prefecture, and Yangzhou Prefecture. During continuous improvements, these facilities exhibited a multi-point-regional aggregation phenomenon.The influence of commercial development indicator on the spatial distribution of water engineering facilities is positively correlated in both the Ming and Qing dynasties. However, the impacts of the indicator on different types of water engineering facilities vary between the two dynasties. During the Ming Dynasty, the indicators of transportation accessibility and cultural prosperity facilitated the construction of regional water engineering facilities, whereas in the Qing Dynasty, they significantly influenced several types of water engineering facilities. During the Ming and Qing Dynasties, neither the agricultural development indicator nor the population size indicator significantly affected the distribution of water engineering facilities. However, there was a negative correlation between the population size indicator and the distribution of water distribution facilities in the Ming Dynasty. This study enhances the importance of environmental protection in historical societies and provides a valuable reference for other international studies of linear cultural and material heritage.